2009
DOI: 10.1063/1.3065480
|View full text |Cite
|
Sign up to set email alerts
|

Laminated, microfluidic-integrated carbon nanotube based biosensors

Abstract: In this communication, a laminated, flexible, microfluidic-integrated, all CNT based liquid-gated transistor and biosensor are reported that comprises single walled CNTs for both the semiconducting channel as well as the contact electrodes. The proposed architecture eliminates the need for lithography, electrode definition processes, and also circumvents substrate surface compatibility issues. Real-time detection of 1 pM poly-L-lysine in a liquid-gated transistor comprising only two materials, single walled CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…4). Of these possible mechanisms, a series of studies have shown that the predominant sensing mechanism in LGFET comes from electrostatic gating (Curreli et al 2008;Li et al 2005;Maehashi et al 2006;Tey et al 2009;Wijaya et al 2009) and/or Schottky barrier modulation (Gui et al 2007;Byon and Choi 2006).…”
Section: Sensing Mechanisms In Lgfet-based Biosensorsmentioning
confidence: 98%
See 1 more Smart Citation
“…4). Of these possible mechanisms, a series of studies have shown that the predominant sensing mechanism in LGFET comes from electrostatic gating (Curreli et al 2008;Li et al 2005;Maehashi et al 2006;Tey et al 2009;Wijaya et al 2009) and/or Schottky barrier modulation (Gui et al 2007;Byon and Choi 2006).…”
Section: Sensing Mechanisms In Lgfet-based Biosensorsmentioning
confidence: 98%
“…However, the use of planar substrate instead of the nanostructured material as the sensing element might limit the achievable sensitivity of the platform. Figure 6c shows another approach using a two-step lamination process for LGFET fabrication (Tey et al 2009), in which the use of silicon substrate is no longer required. The detailed fabrication process of this laminated CNT-LGFET is exemplified in Fig.…”
Section: Design and Fabrication Of Microfluidic-integrated Fetsmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have attracted interest in biosensing applications [32][33][34][35]. For example, CNT biosensors were used for real-time detection of poly-L-lysine with a detection limit of ∼1 pM [32]. In [34], CNT FET device networks were found to be extremely sensitive to the addition of ultralow concentrations of DNA, down to 0.1 fM, which is equivalent to ∼100 DNA molecules.…”
Section: Figure B4mentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have attracted interest in biosensing applications [32][33][34][35]. For example, CNT biosensors were used for real-time detection of poly-L-lysine with a detection limit of ∼1 pM [32].…”
Section: Figure B4mentioning
confidence: 99%
“…In electronic impedance spectroscopy method, the carbohydrate modified boron doped diamond surfaces have been used to investigate carbohydrate-protein interactions [15]. Due to the excellent electronic properties of the SWNTs, the field effect transistor (FET) 3 made of SWNTs and chemically modified SWNTs were used as protein biosensors [16,17].…”
mentioning
confidence: 99%